2018
DOI: 10.1088/1361-6498/aaac3b
|View full text |Cite
|
Sign up to set email alerts
|

Radiation situation dynamics at the Andreeva Bay site for temporary storage of spent nuclear fuel and radioactive waste over the period 2002–2016

Abstract: The Coastal Technical Base (CTB) №569 at Andreeva Bay was established in the early 1960s and intended for the refueling of nuclear submarine reactors and temporary storage of spent nuclear fuel (SNF) and radioactive waste (RW). In 2001, the base was transferred to the Russian Ministry for Atomic Energy and the site remediation began. The paper describes in detail the radiation situation change at the technical site in Andreeva Bay from 2002–2016, the period of preparation for the most critical phase of remedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In 2002, at the moment of the remediation beginning, almost all buildings and constructions of the facility were in emergency conditions, under degradation and continuously contaminated the environment [27]. The remediation of the facility continues today, the appropriate infrastructure is created for removal of SNF and radioactive waste (RW) [3,28].…”
Section: Results For the Andreeva Bay Nwc Sevrao Technical Sitementioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, at the moment of the remediation beginning, almost all buildings and constructions of the facility were in emergency conditions, under degradation and continuously contaminated the environment [27]. The remediation of the facility continues today, the appropriate infrastructure is created for removal of SNF and radioactive waste (RW) [3,28].…”
Section: Results For the Andreeva Bay Nwc Sevrao Technical Sitementioning
confidence: 99%
“…This case exists for a nuclear legacy site called Andreeva Bay facility under the Northwest Center for Radioactive Waste Management SevRAO-a branch of the Federal State Unitary Enterprise the Enterprise for Radioactive Waste Management RosRAO (hereinafter referred to as Andreeva Bay NWC SevRAO). According to [3] 137 Cs is the main doseforming radionuclide for Andreeva Bay NWC SevRAO.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is easy to calculate that 37 empirical distributions of daily doses of the US-605 personnel are the implementation of the normal distribution, 15 are the implementation of the Weibull distribution and 27 are the implementation of the normal composition with a discrete two-digit distribution. Let us consider the second set of data on daily doses of the personnel of the Andreeva Bay NWC SevRAO Facility, which were obtained under the conditions of professional exposure of the personnel in 2016 [17]. The number of the personnel of this facility did not exceed a hundred people.…”
Section: Results For Occupational Dose Distributions Analysismentioning
confidence: 99%
“…Testing of radionuclide sorption between groundwater and soil showed that there would be migration of contamination via groundwater to the offshore marine environment. With the possibility of further contamination occurring because of radionuclide migration, dynamic surveillance has been necessary to monitor the radiation situation both during routine activities at the site, and during the process of spent nuclear fuel and radioactive waste removal (Chizhov et al 2018).…”
Section: Providing Proper Remediation Monitoring and Compliance Checkingmentioning
confidence: 99%